Trends in consuming alcoholic beverages among adolescents and young adults of school age: sexes differences - Rachel Mola; Rodrigo Cappato de Araújo; Shayra Anny Barbosa; Layane Sá Almeida; Ana Carolina Rodarti Pitangui (Elsevier, 2023)
Objective: To analyze the tendency of alcoholic beverage consumption among adolescents and young adults at school age according to their sexes. Methods: This is a trend research study in public schools of the municipality of Petrolina, between 2014 and 2016, with 3146 students aged between 12 and 24 years old. The instrument was constituted by socio-economic inquiry and the Youth Risk Behavior Survey. Trends were assessed using the Centers for Disease Control and Prevention recommended approach. The analyses were conducted using logistic regression, with a statistical significance of 0.05. Results: Close to 56% of the adolescents had already tried some alcoholic beverage, most of which had contact after 13 years of age. The prevalence of binge drinking ranged between 17% and 25%. The percentage of girls who tried alcohol before 13 years old remained similar over the three years (p = 0.943). The prevalence of this behavior was stabilized at around 20%. There was a trend to decrease in the prevalence of boys who reported having tried alcohol before 13 years old (p = 0.014). The percentage of boys who reported involvement in binge drinking in the past 30 days remained stable at around 20% over the years (p = 0.951). The girls' data revealed a significant decrease in binge drinking (p = 0.019). Conclusions: The general analysis suggests a trend towards stabilization of consumption among boys, and an increase among girls.